Assessment of histological and immunohistochemical features of retinal tissues using a novel tissue submission procedure. (February 2023) - Wang, Lei-Chi; Lo, Wen-Jung; Chou, Yu-Bai; Chen, Shih-Jen; Lin, Tai-Chi; Chou, Teh-Ying
Abstract: We introduce a novel tissue submission procedure without additional equipment or storage facilities for assessing the histological and immunohistochemical features of retinal tissues. In total, 150 specimens were collected from patients who underwent vitrectomy or macular surgery from January to December 2020. Ninety-eight specimens were submitted using the new procedure, and 58 specimens were submitted as flat-mount slides to compare specimen adequacy. The tissues submitted using the new procedure were subjected to paraffin-embedding and sectioning for hematoxylin & eosin staining. Additional immunohistochemical analysis was performed to assess the cellular composition in retinal tissues with diverse etiologies. The new submission procedure had an adequacy ratio of 75.51%, which was comparable to that of the flat-mount method ( p  = 0.1397). The new method could produce high-quality images of histological features of tissues and facilitated immunohistochemical analysis to demonstrate cell origins. More glial cells ( p  = 0.000) and myofibroblasts ( p  = 0.012) were detected in the epiretinal membranes (ERMs) than in the internal limiting membranes (ILMs). Subgroup analysis revealed that secondary ERMs contained more macrophage-like cells ( p  = 0.001) and retinal pigment epithelial cells ( p  = 0.000) than did idiopathic ERMs. Our novel tissue submission procedure can be applied to routine clinical practice. Our study provides additional histological and immunohistochemical evidence of cellular components in retinal tissues based on a large number of human tissue samples. Moreover, tissues submitted using the new method can be permanently preserved, enabling future investigation for potential prognostic or therapeutic targets. Highlights: We report a feasible method for assessing human retinal tissues without requiring additional facilities.